Effect of Sucrose and Starter on the Chemical and Organoleptic Properties of Fig Leaf Tea Water Kefir - SY, Muhammad Zakwan Saputra; Wardani, Agustin Krisna (agriTECH, 2024)
Water kefir is a fermented drink made by adding water kefir grains to a water solution containing dried fruit or sugar. This research aims to determine the effect of sucrose, starter, and interactions on the chemical characteristics (antioxidant activity, total acid, medium pH) and organoleptics of fig leaf tea water kefir and to determine the interaction of antioxidant activity with total acid and medium pH. The experiment used variations in starter concentration (5% and 8%) and sucrose concentration (3%, 6%, 9% and 12%). Water kefir was analyzed through chemical analysis (antioxidants, total acid, medium pH, and sugar content) and organoleptic tests (flavor, aroma, color, and overall preference). The results showed that variations in the addition of sucrose, starter, and interactions influenced the metabolic results (primary and secondary metabolites) of microorganisms in water kefir grains and statically had a significant effect on changes in chemical and organoleptic properties (flavor, aroma, and overall preference). The best chemical characteristic parameters were obtained in the B2S3 treatment (8% starter + 9% sucrose) with antioxidant activity of 51.27%, total acid of 0.70%, and medium pH of 3.53. Meanwhile, the best organoleptic parameters were obtained in the B2S4 treatment (8% starter + 12% sucrose) with a taste value of 5.56 (liked), an aroma value of 4.80 (slightly liked), a color value of 4.97 (slightly liked), and the overall liking level was 5.45 (liked), and the antioxidant activity of fig leaf tea water kefir had a strong relationship with total acid and medium pH. Furthermore, the addition of sucrose and different starters during the water kefir fermentation process affects the chemical and organoleptic properties of fig leaf tea water kefir. It is hoped that the results of this research will make fig leaf tea water kefir an alternative probiotic drink for sufferers of lactose intolerance and allergies to milk-based drinks.